THE INFLUENCE OF SERVICE QUALITY AND BRAND IMAGE ON CONSUMER LOYALTY AT PT. MITRA BINTANG CARGOTAMA - Angelina, Celine (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
In today's era, business competition has grown rapidly, this makes companies very competitive in understanding what consumers expect from the services the company provides and providing attractive offers to get a positive assessment from consumers to improve its brand image. Therefore, the purpose of this study was to determine the effect of service quality and brand image on consumer loyalty at PT. Mitra Bintang Cargotama. This study uses descriptive qualitative research methods using primary data sources. The data were analyzed descriptively qualitatively. The results of this study were obtained through interviews and distributing questionnaires to respondents. This type of research uses a sampling method, namely non-probability sampling with a saturated sample type for data collection. This research includes multiple regression analysis.